Polarimetric analysis of STEREO observations of sungrazing kreutz comet C/2010 E6 (STEREO). Issue 2 (19th April 2022) - Nežič, Rok; Bagnulo, Stefano; Jones, Geraint H; Knight, Matthew M; Borisov, Galin
ABSTRACT: Twin STEREO spacecraft pre-perihelion photometric and polarimetric observations of the sungrazing Kreutz comet C/2010 E6 (STEREO) in March 2010 at heliocentric distances 3−28 R⊙ were investigated using a newly created set of analysis routines. The comet fully disintegrated during its perihelion passage. Prior to that, a broadening and an increase of the intensity peak with decreasing heliocentric distance was accompanied by a drop to zero polarization at high phase angles (∼105°–135°, STEREO-B ) and the emergence of negative polarization at low phase angles (∼25°–35°, STEREO-A ). Outside the near-comet region, the tail exhibited a steep slope of increasing polarization with increasing cometocentric distance, with the slope becoming less prominent as the comet approached the Sun. The steep slope may be attributed to sublimation of refractory organic matrix and the processing of dust grains, or to presence of amorphous carbon. The change in slope with proximity to the Sun is likely caused by the gradual sublimation of all refractory material. The polarization signatures observed at both sets of phase angles closer to the comet photocentre as the comet approached the Sun are best explained by fragmentation of the nucleus, exposing fresh Mg-rich silicate particles, followed by their gradual sublimation. The need for further studies of such comets, both observational and theoretical, is highlighted, as well as the benefit of the analysis routines created for this work.